Evaluation of Organic Amendments against Rice Root-KnotNematode at Seedling Stage of Rice - Dangal, Nabin Kumar; Poudyal, D. Sharma; Shrestha, S. M.; Adhikari, C.; Duxbury, J. M.; Lauren, J. G. (Nepal Journal of Science and Technology, 2010)
Pot experiment was conducted during July-September 2006 to evaluate some organic amendments such as sesame (Sesamum indicum) biomass, buckwheat (Fagopyrum esculentum) biomass, neem (Azadirachta indica) leaves, chinaberry (Melia azedarch) leaves and chicken manure @ 1, 2 and 3 t ha-1 each against the rice root-knot nematode (Meloidogyne graminicola Golden & Birchfield) in direct seeded rice. The treatments were replicated five times in a randomized complete block design. The number of second stage juveniles (J2) of M. graminicola was significantly low in chicken manure @ 3 t ha-1. The root knot severity index was significantly low in sesame @ 3 t ha-1, chinaberry @ 3, 2 or 1 t ha-1, neem @ 3 t ha-1 and chicken manure @ 2 or 3 t ha-1 amended soil but root lesion severity index was lower only in chicken manure @ 2 t ha-1 treated plots. The fresh shoot weight and length were significantly high in chicken manure amendment @ 2 or 3 t ha-1 at 45th day after seeding. However, the fresh root weight, length, number of leaves and number of J2 recovered from the roots were non-significant. Key words: biomass; juveniles; Meloidogyne graminicola; root-knot severity index; root lesion severity index DOI: 10.3126/njst.v9i0.3160 Nepal Journal of Science and Technology 9 (2008) 21-27